Prediction of Self Life of Kemplang Crackers Packaged in Polypropylene Plastick with Thickneses - Astrid Wulandari; Sri Waluyo; Dwi Dian Novita (The University of Lampung, 2013)
Kemplang crackers are classified as absortive food. This may cause kemplang crackers are easly soggy and their texture become tougher and chewier. The objective of this research was to predict the self life of packaged kemplang crackers placed in different storage conditions. Kemplang crackers were stored in a polypropylene (PP) plastic with three different thicknesses : 0,3 mm, 0,5 mm and 0,7 mm and relative humidity (RH) of about 63% and about 53%. The packages were stored in ambient temperature. The results showed that kemplang crackers stored at lower RH and thicker plastick have a longer self life. The self life of kemplang cracker stored in PP plastic with thickness of 0,3 mm, 0,5 mm, and 0,7 mm and in ambient RH were 12 days, 14 days, and 33 days, respectively, while the self life of kemplang cracker storaged in PP plastic with thickness of 0,3 mm, 0,5 mm, and 0,7 mm and RH of about 53% were ranging from 185 days to more than >365 days. Keywords: Kemplang Crackers, Polypropylene Plastic, Self -life